2019
DOI: 10.1111/resp.13668
|View full text |Cite
|
Sign up to set email alerts
|

Analysis by proteomics reveals unique circulatory proteins in idiopathic pulmonary fibrosis

Abstract: Background and objective: Idiopathic pulmonary fibrosis (IPF) is a progressive fibrotic disease that has a poor 3-year median survival rate with unclear pathophysiology. Radiological features include bibasal, subpleural fibrosis and honeycombing while its pathology is characterized by fibroblastic foci and honeycombing. Proteomic analysis of circulating molecules in plasma may identify factors that characterize IPF and may assist in the diagnosis, prognostication and determination of pathogenic pathways in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 20 publications
(24 reference statements)
2
8
0
Order By: Relevance
“…Fibronectin-EDA is enriched at sites where tissue remodelling due to inflammation is present and has the ability to activate the immune system by binding TLR4, thereby acting as a DAMP [234,235]. Although the levels of fibronectin-EDA have not been measured in extracellular fluids of IPF patients to date, using a targeted mass-spectrometry approach it was shown that the plasma levels of fibronectin were significantly lower in plasma of IPF patients compared with matched healthy controls [236]. In contrast, the levels of fibronectin in BALF were shown to be two-to three-fold increased in IPF patients compared with healthy controls [237].…”
Section: Ecm-derived Damps Inducing Pro-inflammatory Responses In Ipfmentioning
confidence: 99%
“…Fibronectin-EDA is enriched at sites where tissue remodelling due to inflammation is present and has the ability to activate the immune system by binding TLR4, thereby acting as a DAMP [234,235]. Although the levels of fibronectin-EDA have not been measured in extracellular fluids of IPF patients to date, using a targeted mass-spectrometry approach it was shown that the plasma levels of fibronectin were significantly lower in plasma of IPF patients compared with matched healthy controls [236]. In contrast, the levels of fibronectin in BALF were shown to be two-to three-fold increased in IPF patients compared with healthy controls [237].…”
Section: Ecm-derived Damps Inducing Pro-inflammatory Responses In Ipfmentioning
confidence: 99%
“…Thus, this tool has both facilitated and hastened the identification of key proteins involved in the progression of different diseases [7,11]. Coincidently, several investigations on IPF have used proteomic approaches to characterize the molecular mechanisms involved in the disease progression [2,3,7,[12][13][14][15][16]; however, limited studies have aimed to identify the proteomic profile of EVs cargo secreted during IPF progression [8]. Thus, here we identified differentially expressed proteins contained within EVs cargo secreted by cell lines isolated from lungs bearing IPF.…”
Section: Introductionmentioning
confidence: 99%
“…Since two‐dimensional electrophoresis is a semiquantitative method, here we used quantitative ELISA to corroborate these findings and to detect higher ATIII concentrations in IFP patients than in controls. Although the role of ATIII in the pathogenesis and course of IPF has only been partly explored, 20,21 our findings suggest that this serine protease inhibitor, with anticoagulant and anti‐inflammatory functions, could have a useful role in monitoring IPF patients treated with nintedanib. To our knowledge, this is the first study reporting quantitative changes in ATIII concentrations in response to nintedanib therapy.…”
Section: Discussionmentioning
confidence: 85%